Developing an Inclusive Numeracy Assessment for a Blind Student in using the ADDIE Model - Arrumaisha Nur Rahmah; Endang Rochyadi; Nadiyah 'Ufairah Muqsithah AM; Widya Annisa Sari; Nita Nitiya Intan Tanbrin (LP. Ma'arif Janggan Magetan, 2025)
In a society where numbers and visual representations dominate daily life, how can one assess the numeracy skills of children who are unable to perceive numbers visually? This critical question served as the foundation for research that sought to reconceptualize the nature of mathematics assessment for students with visual impairments. The primary aim of the research was to design a numeracy assessment instrument that is not only valid and reliable but also empathetic and responsive to the sensory needs of these learners. To achieve this, the instrument was developed by integrating the ADDIE instructional design model with the inclusive Merdeka Curriculum, while adapting numeracy indicators derived from the theoretical frameworks of Piaget and Bloom to suit the characteristics of visually impaired students. The results demonstrate that the finalized instrument, comprising 48 validated items tested with a visually impaired student, effectively measures numeracy competencies. This research contributes to the field by introducing a curriculum-based, multisensory assessment tool specifically created for visually impaired students in the Indonesian context.